AN ANALYSIS OF THE ROLE OF INSURANCE FROM PT. JASA RAHARJA IN COVERING THE INPATIENT COSTS OF TRAFFIC ACCIDENT VICTIMS IN PEKANBARU CITY - Abdul Kudus Zaini; Muhammad Zainal Muttaqin (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Traffic accidents impose a heavy economic burden, particularly on victims’ medical expenses. PT. Jasa Raharja, a state-owned insurance company, plays a crucial role in providing compensation for hospitalization costs. This study analyzes the impact of PT. Jasa Raharja’s insurance on inpatient expenses for traffic accident victims in Pekanbaru City. The research applies a quantitative approach with descriptive analysis and simple regression. Data came from 120 respondents, consisting of victims and their families who received insurance benefits. The findings show that PT. Jasa Raharja’s insurance claims cover an average of 67% of total hospitalization costs, significantly reducing the victims’ financial burden. However, the coverage ceiling remains limited and does not fully meet medical expenses. This study concludes that PT. Jasa Raharja makes a substantial contribution to financing accident-related hospitalization, although increasing the claim ceiling would better align with current hospital costs.